Clusia heterocolorata (Clusiaceae), a new species from the Brazilian Atlantic Forest - Marinho, Lucas Cardoso; Amorim, André M.; Bittrich, Volker (Phytotaxa, 2015)
Clusia heterocolorata is described, illustrated, its diagnostic characteristics, morphological affinities, and conservation status are discussed, and a geographical distribution map is presented. This new species belongs to the section Phloianthera, characterized by a dome-shaped androecium with numerous resiniferous stamens and staminodes.